The Clinical Utility of Cell-Free DNA Measurement in Differentiated Thyroid Cancer: A Systematic Review - Fussey, Jonathan M.; Bryant, Jennifer L.; Batis, Nikolaos; Spruce, Rachael J.; Hartley, Andrew; Good, James S.; McCabe, Christopher J.; Boelaert, Kristien; Sharma, Neil; Mehanna, Hisham (Frontiers in Oncology, 2018)
Background: Cell-free DNA can be detected in the circulation of healthy individuals, but is found in higher concentrations in cancer patients. Furthermore, mutations in tumour cells can be identified in circulating DNA fragments. This has been the subject of significant interest in the field of cancer research, but little has been published in thyroid cancer. Objectives: To assess all available evidence on the use of circulating cell-free DNA in the diagnosis, management and surveillance of patients with differentiated thyroid cancer, and collate it into a systematic review to guide future research. Methods: A comprehensive literature search on the measurement of cell-free DNA in thyroid cancer was undertaken, and results from relevant studies collated into a systematic review. Results: Nine studies were identified, with varying methodologies and findings. Key techniques and findings are summarised. Conclusions: There is limited but promising evidence that somatic mutations in thyroid cancer can be detected in circulating cell-free DNA, and are associated with more advanced disease. Further research is required to develop a clinically useful tool based on cell-free DNA to improve the management of thyroid cancers.